Beyond Styles: An Integrative Framework of Educational Leadership Theories and Models - Afra Fitriani; Ni Putu Saras Dewi; Henny Suharyati (Al-Qalam Institue, 2025)
This study aims to clarify which leadership configurations most effectively enhance teaching quality and student outcomes in schools. Using a structured literature review guided by PRISMA, we searched Scopus, ERIC, Web of Science, Garuda, and Google Scholar (2014–2024) with Indonesian/English keywords on instructional, transformational, servant/teacher, distributed/visionary, and transactional leadership. Inclusion criteria were peer-reviewed journal articles in educational contexts with clear theoretical grounding and/or empirical evidence; records were screened, full texts appraised (JBI/MMAT), and findings synthesized thematically. Results indicate that no single style is sufficient. The most consistent gains arise from an integrated configuration: (a) instructional leadership to set academic goals, conduct classroom observation–feedback, and align curriculum–assessment; (b) transformational leadership—especially idealized influence, inspirational motivation, and intellectual stimulation—to build commitment and innovation; (c) servant/teacher leadership to strengthen psychological safety and professional ownership; and (d) distributed/visionary structures to secure continuity and strategic direction, with transactional elements used to maintain procedural reliability. This configuration converts trust into classroom practice via data-informed coaching and protected time for PLCs. Implications include designing leadership development that couples moral–relational competencies with auditable instructional routines, revising accreditation to value classroom practice evidence, and investing in data literacy and digital tools to support evidence-based instructional decisions.